Rehabilitation of facial defect on a unique case of disfigurement - Chithambaradhas Sivakala Arunkumar; J Brintha Jei; Murugesan Krishnan; Balasubramaniam Muthukumar (Wolters Kluwer Medknow Publications, 2021)
Rehabilitation of facial disfigurement after a surgery or trauma is difficult to address as it involves individuality of the patient. Face being the visual pro forma, rehabilitating it is always a challenging task. This is predominantly due to the presence of soft tissue, lack of anatomic undercut, and increased muscle activity. The use of osseointegrated implants provides the most reliable retention, however, placing it on an intact facial defect further complicates rehabilitation. This case report is about rehabilitation of lost facial feature after tumor resection surgery.